MENINGKATKAN KEMAMPUAN GEOMETRI ANAK USIA 4-5 TAHUN MELALUI PERMAINAN KOTAK PAS DI TK PEMBINA NEGERI 1 BANGKO KABUPATEN ROKAN HILIR - Rahayu, Sri; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this study was to determine the ability of children’s geometry 4-5 years at TK Pembina Negeri 1 Bangko Rokan Hilir Regency by game of shape sorting cube, to determine how the application of shape sorting cube game was improved the ability of children’s geometry 4-5 years at TK Pembina Negeri 1 Bangko Rokan Hilir Regency, as well as to determine whether the shape sorting cube game can improve children’s geometry at TK Pembina Negeri 1 Bangko Rokan Hilir Regency. Based on the results of a classroom action research that has been conducted at TK Pembina Negeri 1 Bangko Rokan Hilir Regency, the ability of children’s geometry were increased through the application of shape sorting cube game on children 4-5 years whether done by groups or individuals. Percentage the ability of children’s geometry 4-5 years at TK Pembina Negeri 1 Bangko Rokan Hilir Regency were increased from 38.33% before the cycle into 52.41% in first cycle and 75.93% in second cycle. The largest percentage increased in the ability of children’s geometry 4-5 years by using media shape sorting cube game is 98.07% (prior cycle to cycle II).Keyword : Children 4-5 Years, Ability Of Children’s Geometry, Shape Sorting Cube Game